European Lifelong learning policies. The case of Lifelong Learning Centre of University of Macedonia in Greece - Kavasakalis, Aggelos; Papadimitriou, Maria (Advances in Social Sciences Research Journal, 2022)
The paper focuses on the implementation of lifelong learning policies (LLL) in Greek universities concerning the establishment and operation of lifelong learning centres (LLLCs) in universities. The research will focus on the characteristics of the active curricula in the academic year 2020-21 of one lifelong learning centre, the centre of the University of Macedonia. Specifically, the first section makes a reference to knowledge society and its characteristics and provides the basic definitions of the concepts that will be dealt with in the article. The 2nd section highlights the main developments in lifelong learning policies, initially at a European level and subsequently at a national level. The 3rd section presents the research methodology concerning the characteristics and central choices of the lifelong learning centre of the University of Macedonia. The 4th section presents the analysis of the survey findings and our conclusions.